Political Control of the Constitutionality of Laws - The French Constitutional Council as a Model - Tebina, Hakim (Journal of Legal Studies and Researches, 2020)
The French constitutional institution adopted the method of political control over the constitutionality of laws through the establishment of the constitutional council as independent political parties due to the lack of confidence in the judicial authority, and thus with the aim of protecting the basic rights and freedoms of individuals and ensuring respect for the principle of the constitution. The problem of this study revolves around the effectiveness of the mechanisms on which the Constitutional Council depends on the exercise of its oversight role in order to consecrate its political character? In order to deal with the issue in various aspects, the descriptive approach to this study was adopted in addition to the analytical approach in dealing with the legal texts and we concluded that the lack of previous political control exercised by the Constitutional Council according to the notification mechanism was the reason for activating subsequent judicial review of the constitutionality of laws, by recognizing the right of individuals to litigate in front the Constitutional Council indirectly through the Priority issue of constitutionality.